Predictive Value of Three-Dimensional Transvaginal Sonography for Staging of Endometrial Neoplasia. (November 2018) - Fernandez, Carlos M.; Levine, Elliot M.; Dini, Morteza; Bannon, Kimberly; Butler, Stacy; Locher, Stephen
The goal of this study was to compare the sonographic assessment of endometrial cancer diagnosis and staging using three-dimensional transvaginal sonography with the staging that was ultimately found at surgery. Three-dimensional transvaginal sonography was performed for 20 consecutive cases of presumptive endometrial cancer using power Doppler angiography, virtual organ computer-aided analysis, and volume contrast imaging. These results were compared with the surgical staging found for those identified cases. The sonographic findings predicted the correct minimum endometrial cancer staging in 100% of the 20 cases that were examined and correlated to surgical outcomes. The successful prediction of endometrial cancer staging demonstrated by others was replicated in the organization of this case series. The findings compared favorably with other imaging modalities used for this purpose. This study assists in demonstrating the value of using presurgical three-dimensional sonography to plan for the optimal surgical excision and overall treatment of endometrial cancer.